Green manufacturing fundamentals and applications - Dornfeld, David A. (Springer, 2013)
Green Manufacturing: Fundamentals and Applications introduces the basic definitions and issues surrounding green manufacturing at the process, machine and system (including supply chain) levels. It also shows, by way of several examples from different industry sectors, the potential for substantial improvement and the paths to achieve the improvement. Additionally, this book discusses regulatory and government motivations for green manufacturing and outlines the path for making manufacturing more green as well as making production more sustainable.